Archeological Survey and Site Testing for the Joshua Tree Roads Project, Package 291, Joshua Tree National Park, California - Neff, Loy C.; Corey, Christopher C. (the Digital Archaeological Record)
TWO reports in one volume: Part 1: Archeological Survey and Site Assessments for the Joshua Tree Roads Project, Package 291, Joshua Tree National Park, California Archeologists from the National Park Service (NPS), Western Archeological and Conservation Center (WACC), conducted archeological survey and site assessments in the roadway corridor, or area of potential effects (APE), of a proposed road construction project in Joshua Tree National Park (JOTR), California. The road construction is identified as Joshua Tree Roads Project, Package 291 (Pkg. 291) and is part of a series of road construction and improvement projects along Park Boulevard (Rte. 12). The Pkg. 291-road construction is scheduled to begin after the completion of the on-going road construction project (Pkg. 173) between Quail Springs and Cap Rock. The Pkg. 291-road construction will continue from Cap Rock to Geology Tour Road, a distance of nearly six miles. Part 2: Archeological Site Testing and Recommendations for the Joshua Tree Roads Project, Package 291, Joshua Tree National Park, California Archeologists from the National Park Service (NPS), Western Archeological and Conservation Center (WACC), conducted archeological testing at four sites in Joshua Tree National Park, California, in the area of potential effects (APE) of the proposed road construction project, Joshua Tree Roads Project, Package 291 (Pkg. 291). The sites are threatened by direct and indirect impacts on the resources from the proposed construction. The Pkg. 291-road project is part of a series of road construction and improvement projects along Park Boulevard (Rte. 12) in the northwestern Park. The Pkg. 291-road construction is scheduled to begin in the summer of 2002. The Pkg. 291-road project extends from Cap Rock to Geology Tour Road, a distance of nearly six miles.